Gasdermin E links tumor cell-intrinsic nucleic acid signaling to proinflammatory cell death for successful checkpoint inhibitor cancer immunotherapy - Stefan Enssle; Anna Sax; Peter May; Nadia El Khawanky; Nardine Soliman; Markus Perl; Julius C. Enssle; Karsten Krey; Jürgen Ruland; Andreas Pichlmair; Florian Bassermann; Hendrik Poeck; et al. (OncoImmunology)
Durable clinical responses to immune checkpoint inhibitors (ICI) are limited to a minority of patients, and molecular pathways that modulate their efficacy remain incompletely defined. We have recently shown that activation of the innate RNA-sensing receptor RIG-I and associated apoptotic tumor cell death can facilitate tumor immunosurveillance and -therapy, but the mechanism that drives its immunogenicity remained unclear. We here show that intratumoral activity of the pore-forming protein gasdermin E (GSDME) links active RIG-I signaling and apoptotic cell death in tumor cells to inflammatory pyroptosis. Activation of tumor-intrinsic RIG‑I triggered cleavage of GSDME, pore formation, loss of cell membrane integrity and leakage of cytosolic components from dying tumor cells. Tumor antigen cross-presentation by dendritic cells and subsequent expansion of cytotoxic T cells strongly relied on tumor-intrinsic GSDME activity. In preclinical murine cancer models, defective GSDME signaling rendered tumors resistant to ICI therapy. Epigenetic reprogramming with upregulation of Gdsme enhanced the susceptibility of tumor cells to inflammatory cell death and immunotherapy. In humans, transcriptome analysis of melanoma samples showed strong correlation between genetic activity of the RIG-I and pyroptosis pathways. In melanoma patients, high transcriptional activity of a pyroptosis gene set was associated with prolonged survival and beneficial response to ICI therapy. In summary, our data show that GSDME links RIG-I and apoptotic signaling to inflammatory cell death, thereby driving its immunogenicity and responsiveness to ICI. A deeper understanding of these pathways may allow for the development of novel combined modality approaches to improve ICI treatment responses in cancer patients.